Enhanced thermal conductivity of SiCp/PS composites by electrospinning–hot press technique. (December 2015) - Gu, Junwei; Lv, Zhaoyuan; Wu, Yalan; Zhao, Ruoxi; Tian, Lidong; Zhang, Qiuyu
Abstract: Silicon carbide particle/polystyrene (SiCp/PS) electrospun mats are firstly prepared by electrospinning technology, then to be fabricated the corresponding thermally conductive SiCp/PS composites by the method of "laminating-hot press". The mass fraction of SiCp and laminating mode of SiCp/PS electrospun mats affecting on the thermal conductivities, dielectric and thermal properties of the composites are investigated. The addition of 32.8 vol% SiCp improves the thermally conductive coefficient λ of pure PS from 0.182 to 0.566 W/m K and thermal diffusivity of pure PS from 0.169 to 0.376 mm 2 /s, whereas the dielectric constant values still remain at relatively low levels. The thermal stabilities of the SiCp/PS composites are increased with the increasing addition of SiCp. For a given SiCp loading, the SiCp/PS composites from warp–weft arrangement of SiCp/PS electrospun mats possess relative higher thermally conductive coefficient λ and dielectric constant values than those of SiCp/PS composites from warp–warp arrangement of SiCp/PS electrospun mats.